Multi-year weed community dynamics and rice yields as influenced by tillage, crop establishment, and weed control: Implications for rice-maize rotations in the eastern Gangetic plains - Hossain, Khaled; Timsina, Jagadish; Johnson, David E.; Gathala, Mahesh K.; Krupnik, Timothy J. (Diva Enterprises Private Limited, 2020)
In South Asia's rice-based cropping systems, most farmers flood and repetitively till their fields before transplanting. This establishment method, commonly termed puddled transplanted rice (TPR), is costly. In addition, it is labor and energy intensive. To increase labor and energy efficiency in rice production, reduced or zero-tilled direct seeded rice (ZT-DSR) is commonly proposed as an alternative tillage and crop establishment (TCE) option. Effective management of weeds in ZT-DSR however remains a major challenge. We conducted a four-year experiment under a rice-maize rotation in Northwestern Bangladesh in the eastern Gangetic Plains to examine the performance of two TCE methods and three weed management regimes (WMR) on the diversity and competitiveness of weed communities in the rice phase of the rotation. The Shannon-Weiner Diversity Index, a measure of species diversity, was significantly greater under ZT-DSR than puddled TPR. It was also greater under no weed control (Weedy) and two manual weeding (MW) treatments compared to chemical herbicide with manual weeding (C + MW). In DSR Weedy plots, weed communities began shifting from grasses to sedges from the rotation's second year, while in the ZT-DSR and C + MW treatments, sedges were consistently predominant. In both puddled TPR Weedy and TPR C + MW treatments, broadleaves and grasses were dominant in the initial year, while sedges dominated in the final year. There were significant main effects of year (Y) and weed management regime (WMR), but not of TCE. Significant Y × TCE and TCE × WMR interaction effects on rice yield were also observed. Grain yields under ZT-DSR were similar to puddled TPR. ZT-DSR with one application of pre-emergence herbicide followed by one hand weeding at 28 days after establishment however resulted in significantly higher grain yield (5.34 t ha-1) compared the other weed management regimes. Future research should address methods to effectively manage weed community composition shifts in both ZT-DSR and TPR under rice-maize rotations utilizing integrated and low-cost strategies that can be readily applied by farmers in the eastern Gangetic Plains.